Association of lymph vessel density with occult lymph node metastasis and prognosis in oral squamous cell carcinoma - Faustino, Simone E. S.; Tjioe, Kellen C. [UNESP]; Assao, Agnes; Pereira, Michele C.; Carvalho, André L.; Kowalski, Luiz P.; Oliveira, Denise T. (Springer Nature, 2021)
Background: The aims of this study were to determine intra (ILVD) and peritumoral (PLVD) lymphatic vessel density (LVD), and to investigate the relationship of LVD with occult metastasis and prognosis. Methods: Eighty-seven oral squamous cell carcinomas, in clinical stages I or II, arising in the tongue or floor of the mouth were stained with podoplanin. Lymphatic vessels were quantified in intra and peritumoral areas by sequential analysis and hot spot evaluation. Associations of the ILVD and PLVD with clinicopathologic parameters were determined by Chi-square or Fisher’s exact test. The 5 and 10-year survival rates were calculated by the Kaplan–Meier and compared using the log-rank test. Results: No significant association was observed between ILVD or PLDV and clinicopathologic variables including occult lymph node metastasis, or clinical follow-up. However, ILVD showed a significant association with regional recurrence (p = 0.040). The perineural invasion was associated with PLVD (p = 0.041). Disease-specific (p = 0.044) and disease-free survivals (p = 0.016) had significant association with PLVD. Conclusions: The intra or peritumoral lymphatic vessel density had no predictive value for occult lymph node metastasis in the early stages of oral cancer arising in the tongue or floor of mouth.
Keywords: D2-40; Lymphatic metastasis; Oral squamous cell carcinoma; Podoplanin; Prognosis